Prevention and treatment of relapse after stem cell transplantation with immunotherapy. (June 2018) - Gökbuget, Nicola; Canaani, Jonathan; Nagler, Arnon; Bishop, Michael; Kröger, Nicolaus; Avigan, David
Abstract Relapse has become the leading cause of treatment failure after stem cell transplantation. Besides cellular therapies and novel agents, immunotherapeutic strategies have entered clinical practice in order to reduce or prevent relapse. Here, we summarize the presentations on checkpoint inhibitors, vaccination strategies, and novel antibody therapies, which were presented and discussed at the third International Workshop on Biology, Prevention, and Treatment of Relapse after Stem Cell Transplantation.